Service Quality and Brand Trust as Determinants of Customer Loyalty: Mediating Role of Customer Satisfaction - Budi Prasetiyo; Ronny H. Walean; Deske W. Mandagi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Service quality and public trust in government institutions have become pivotal themes in modern marketing discourse, particularly as citizens demand greater efficiency and transparency in public service delivery. This study aims to examine the contribution of service quality and brand trust to customer loyalty, with customer satisfaction as a mediating variable, in the context of the One-Stop Integrated Service Center (PTSP) at the Directorate General of Customs and Excise. Employing a quantitative survey design, data were collected from 85 PTSP service users through purposive sampling. The data were analyzed using structural equation modeling (SEM) to test the hypothesized relationships among variables. The results reveal that service quality and brand trust do not have a significant direct effect on user loyalty. However, customer satisfaction mediates the relationship between service quality and customer loyalty. These findings highlight that enhancing service quality remains essential to increasing satisfaction, which, in turn, drives loyalty among public service users. The study contributes to the growing literature on public sector marketing by underscoring the mediating role of satisfaction and by suggesting the development of stronger brand trust strategies to sustain long-term user engagement in government service context.